Development of the Learning Process of Abhidhanappadipika Scripture - Thumthong, Supee; Paññādīpo, Phramaha Wattana; Suwanprathip, Thanee (Journal of Dhamma for Life, 2025)
This research is a documentary study with the following objectives: 1) to study the Abhidhanappadipikatext, 2) to translate and analyze the content of the Abhidhanappadipika, and 3) to develop a learning process for the Abhidhanappadipika. The research findings reveal that the Abhidhanappadipika, composed by Venerable Moggallana Thera, is a Pali dictionary consisting of 1,203 verses. The text is divided into three sections: (1) Sagga-kanda (Heaven Section), (2) Bhu-kanda (Earth Section), and (3) Samanya-kanda (General Section). The vocabulary in the Abhidhanappadipika aids in the study and research of the Tripitaka and enhances the understanding of Dhamma principles. It includes synonyms (e.g., 32 words meaning "Buddha") and polysemous words (e.g., the word "Dhamma" has over 14 meanings). The development of the learning process for the Abhidhanappadipika was carried out in the following steps: 1) designing an online learning structure divided into 10 sessions, 2) announcing and accepting registrations online, 3) conducting online teaching via Zoom and live-streaming the sessions on Facebook and YouTube, 4) evaluating participants online and awarding certificates, with most participants responding very positively, and 5) after completing the teaching, editing the lecture clips and disseminating them through various media: (1) a website, (2) YouTube, (3) TikTok, and (4) printing and distributing books as Dhamma donations.